Proprioceptive movement illusions due to prolonged stimulation: reversals and aftereffects. - Tatjana Seizova-Cajic (Public Library of Science (PLoS), 2007)
Background Adaptation to constant stimulation has often been used to investigate the mechanisms of perceptual coding, but the adaptive processes within the proprioceptive channels that encode body movement have not been well described. We investigated them using vibration as a stimulus because vibration of muscle tendons results in a powerful illusion of movement. Methodology/principal findings We applied sustained 90 Hz vibratory stimulation to biceps brachii, an elbow flexor and induced the expected illusion of elbow extension (in 12 participants). There was clear evidence of adaptation to the movement signal both during the 6-min long vibration and on its cessation. During vibration, the strong initial illusion of extension waxed and waned, with diminishing duration of periods of illusory movement and occasional reversals in the direction of the illusion. After vibration there was an aftereffect in which the stationary elbow seemed to move into flexion. Muscle activity shows no consistent relationship with the variations in perceived movement. Conclusion We interpret the observed effects as adaptive changes in the central mechanisms that code movement in direction-selective opponent channels.